Metamaterials XIV 2023
DOI: 10.1117/12.2665763
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive biosensor using a Fano resonant asymmetric all-dielectric metasurface

Abstract: Fano resonance is a universal phenomenon that has been widely exploited to achieve spectrally sharp resonances for a variety of applications. Recently, all dielectric metasurface design composed of two silicon resonators, nanodisk and nanobar, exhibits an induced transparency window with ultrahigh quality factor in polarization direction along the nanobar long axis relying on the intriguing physics of Fano resonance. However, the design demonstrates a dispersive behavior within a short spectral range, a phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, structures based on all-dielectric high index material such as the periodic "Lucky knot" shaped nanostructure 40 , split bar resonator 41 , and periodic unit cells of coupled rectangular bar and ring resonators 42 , coupled nano-bar with nanodisk 43 , coupled nano-ellipse with nano-bar 44 , are employed for sensing applications for different materials. All-dielectric structures show enhanced quality factors reaching up to 980 in some cases 41 , however with less sensitivity than their plasmonic counterparts.…”
Section: ∼ 400cmentioning
confidence: 99%
“…On the other hand, structures based on all-dielectric high index material such as the periodic "Lucky knot" shaped nanostructure 40 , split bar resonator 41 , and periodic unit cells of coupled rectangular bar and ring resonators 42 , coupled nano-bar with nanodisk 43 , coupled nano-ellipse with nano-bar 44 , are employed for sensing applications for different materials. All-dielectric structures show enhanced quality factors reaching up to 980 in some cases 41 , however with less sensitivity than their plasmonic counterparts.…”
Section: ∼ 400cmentioning
confidence: 99%
“…At the working wavelength of ( Ξ» = 1.583 ΞΌ m), the structure's sensitivity was (275nm/RIU), resulting in a figure-of-merit (FOM) of (148). Because of its excellent performance and simplicity of manufacture, the suggested design shows great promise for use in refractometric biosensing applications [ 183 ]. In addition, Chen et al presented an all-dielectric metastructure shown in Fig.…”
Section: Classification Of Metamaterials and Metasurfaces In Biosensi...mentioning
confidence: 99%
“…
Fig. 6 Top (a–b) Schematic diagram of the Fano resonant based all dielectric metasurface design [ 183 ]. Bottom (a–b) Schematic representation of a single cycle of the intended meta-structure, which consists of four silicon blocks shaped like sectors and a cross rod positioned on a silica substrate [184] (For interpretation of the references to colour in this figure legend, the reader is referred to the Web version of this article.)
…”
Section: Classification Of Metamaterials and Metasurfaces In Biosensi...mentioning
confidence: 99%